STUDENTS’ UNDERSTANDING OF PRE-ORGANIC CHEMISTRY CONCEPTS: CHEMICAL BONDING - Cesar B Ortiz (State Islamic University of North Sumatra Indonesia, 2019)
Chemical bonding is a basic chemical principle that has applications in many areas of Chemistry. Students of Chemistry need to be able to analyze situations where Chemical bonding occurs in order to understand reaction mechanisms, many physical properties, solubility, molecular interactions and some spectroscopic information. The study investigated the students’ conceptual understanding of pre-organic chemistry concepts in chemical bonding. This used descriptive research design which investigated how the students, after completing General College Chemistry, understand, explain and apply chemical bonding to determine physical attributes of organic molecules. There were 28 BSE Biological Science majors who participated in the study after having completed the 5-units General College Chemistry course with laboratory component. They took the two-tiered conceptual understanding test. The findings show that, generally, the students had functional misconception of Chemical bonding. This manifests that the students had vigorous misconceptions in which they were holding on to their initial beliefs which had enabled them to answer questions correctly, but for wrong reasons. This situation most often goes undetected because usually tests do not probe into the reasons supporting initial students’ response.